The Role of The Family in The Success of Exclusive Breastfeeding - Elvalini Warnelis Sinaga; Mahyunidar Mahyunidar; Risa Tantri Gultom (Contagion: Scientific Periodical Journal of Public Health and Coastal Health, 2023)
Support of others is a key factor for mothers who choose to breastfeed their infants, including those who balance work outside the home and breastfeeding. However, little research has been done to understand how maternal support during the postpartum period impacts mothers' ability to later balance work and breastfeeding, in particular full-time work and exclusive breastfeeding. The results of this qualitative study indicate that the timing of support plays a key role in mothers' ability to successfully overcome barriers during the early postpartum period, thus building maternal self-efficacy in addressing problems encountered when they return to work. Fathers' support can influence mothers' breastfeeding decisions and behavior. Potentially supportive behaviors have been reported in previous studies, but no studies have directly examined which, if any, of those actions are actually more likely to result in desired breastfeeding outcomes. The two studies reported in this paper address this gap by examining relationships between fathers' reported breastfeeding support and mothers' perceptions of received support and breastfeeding intentions, satisfaction, and duration. The Partner Breastfeeding Influence Scale (PBIS) was used in an online survey with 64 women and 41 men (34 couples) and a telephone survey with 80 mothers and 65 fathers (63 couples). Fathers' and mothers' reports of how often fathers engage in the types of support measured by the PBIS were used to predict breastfeeding intentions, satisfaction, and duration. In Study 1, responsiveness predicted breastfeeding success and satisfaction for men and satisfaction for women. However, mothers' intended breastfeeding duration was shorter when fathers both wanted them to breastfeed for a long time and were more appreciative and savvy about breastfeeding. Study 2 showed that the best breastfeeding support is given when a considerate, well-organized teamwork approach is used that is sensitive to the requirements of the mother. Keyword: Breastfeeding, Family, Role, Support, Successfully